Non-alcoholic fatty liver disease and the gut microbiota in adolescents: is there a relationship? - Doaa El Amrousy; Heba El Ashry; Sara Maher; Yousef Elsayed; Samir Hasan (BMC, 2024)
Abstract Background Despite the increasing prevalence of nonalcoholic fatty liver disease (NAFLD), the pathophysiology is still not fully understood. Recent evidence suggests that the gut microbiota may play a role in the pathophysiology of NAFLD and may also offer new therapeutic options. Methods This prospective cross-sectional study included 100 consecutive newly diagnosed obese patients (BMI ≥ 95th percentile), aged 14-18 years with NAFLD (confirmed by ultrasound), persistently elevated levels of alanine aminotransferase (ALT) greater than 60 U/L for 1-6 months, and 100 healthy controls. We evaluated changes in the gut microbiota in NAFLD adolescents compared with healthy controls. Results According to the multiple logistic regressions, the variables associated with NAFLD were the presence of Clostridium difficile, the presence of Salmonella spp., a greater abundance of Bifidobacterium and Prevotella, and a lower abundance of Lactobacillus. Conclusion Changes in the gut microbiota occur in adolescents with NAFLD compared with healthy individuals, which may be useful for identifying youths who are amenable to gut microbiota-based interventions. Clinical trial number Not applicable.